Internal Donors in Ziegler–Natta Systems: is Reduction by AlR3 a Requirement for Donor Clean‐Up?. Issue 5 (8th March 2018) - Zaccaria, Francesco; Vittoria, Antonio; Correa, Andrea; Ehm, Christian; Budzelaar, Peter H. M.; Busico, Vincenzo; Cipullo, Roberta
Abstract: The front cover artwork for issue 5/2018 is provided by the Laboratory of Stereoselective Polymerizations, at the Department of Chemical Sciences, Federico II University of Naples, (Italy). The image shows the reaction deck of a glove‐box‐contained robotic platform used to investigate the chemisorption of Al‐alkyls and organic donors on the surface of Ziegler–Natta polypropylene catalysts. See the Full Paper itself at https://doi.org/10.1002/cctc.201701422 . Abstract : "In this complex catalysis, Al‐alkyls are used to alkylate and reduce the inherently chiral but sterically open surface Ti precursor species, and one or more organic donors co‐adsorbed at neighboring surface locations impart the necessary steric hindrance to the active sites, thus mimicking ancillary ligands in molecular catalysts." This and more about the story behind the research featured on the front cover can be found in this issue's Cover Profile. Read the full text of the corresponding research athttps://doi.org/10.1002/cctc.201701422 .